Shedding New Light on the 18th Dynasty Mummies of the Royal Architect Kha and His Spouse Merit - Bianucci, Raffaella (PLoS One, 2015)
The mummies of Kha and his wife Merit were found intact in an undisturbed tomb in western Thebes near the ancient workers’ village of Deir el-Medina. Previous MDCT (this abbreviation needs spelling out) investigations showed that the bodies of Kha and Merit did not undergo classical royal 18th Dynasty artificial mummification, which included removal of the internal organs. It was, therefore, concluded that the retention of the viscera in the body, combined with an absence of canopic jars in the burial chamber, meant the couple underwent a short and shoddy funerary procedure, despite their relative wealth at death. Nevertheless, all internal organs - brain, ocular bulbs/ocular nerves, thoracic and abdominal organs - showed a very good state of preservation, which contradicts the previous interpretation above. In order to better understand the type of mummification used to embalm these bodies, both wrapped mummies were reinvestigated using new generation X-ray imaging and chemical microanalyses Here we provide evidence that both individuals underwent a relatively high quality of mummification, fundamentally contradicting previous understanding. Elucidated “recipes”, whose components had anti-bacterial and anti-insecticidal properties, were used to treat their bodies. The time and effort undoubtedly employed to embalm both Kha and Merit and the use of imported costly resins, notably Pistacia, do not support the previously held view that the two individuals were poorly mummified. Despite a lack of evisceration, the approach clearly allowed their in situ preservation as well as affording a fairly successful mummification.